(untitled) (Journal of Digital System Development, 2024)
This paper describes Repository for Malaysia Herbs, a mobile application system used to view information on Malaysian herbs and make purchases through this platform. This project aims to develop a mobile application that provides information to everyone interested in Malaysian spices. The methodology used in this project is known as the Agile method, which involves six phases: planning, designing, developing, testing, reviewing, and launching. Besides, this project will increase people’s knowledge about and expand Malaysian herbs abroad. In conclusion, this project has successfully developed all the basic features that allow users to search for and understand the information on herbs herbsand purchase them through this platform.